An Update on Epidemiology and Management Trends of Vestibular Schwannomas. Issue 3 (March 2020) - Pandrangi, Vivek C.; Han, Albert Y.; Alonso, Jose E.; Peng, Kevin A.; St. John, Maie A.
Abstract : Objective: To determine the current epidemiology and management trends for patients with vestibular schwannomas (VS). Study Design: Retrospective cohort study. Setting: The Surveillance, Epidemiology, and End Results (SEER) tumor registry. Patients: The SEER database was queried to identify patients diagnosed with VS from 1973 to 2015. Demographics, patient and tumor characteristics, and treatment methods were analyzed. Results: A total of 14, 507 patients with VS were identified. The mean age at diagnosis was 55 ± 14.9 years. Age-adjusted incidence from 2006 to 2015 was 1.4 per 100, 000 per year and remained relatively stable. Incidence across age varied with sex, as younger women and older men had increased incidences comparatively. A higher percentage of patients underwent surgery alone (43%), followed by observation (32%), radiation alone (23%), and combined radiation and surgery (2%). Age 65 and older was associated with observation (odds ratio [OR] 1.417; p = 0.029) whereas age 20 to 39 and 40 to 49 were associated with surgery (OR 2.013 and 1.935; p < 0.001). Older age was associated with radiation. Larger tumor size was associated with surgery and combined treatment. African American patients and American Indian or Alaskan Native patients were more likely to undergo observation than surgery. Conclusions: The overall incidence of VS is 1.4 per 100, 000 per year and has remained relatively stable. There is a trend toward more conservative management with observation, which may be secondary to earlier diagnosis given widespread use of magnetic resonance imaging. Further studies are necessary to investigate differences in disease patterns and disparities in management. Abstract : Supplemental Digital Content is available in the text